ARTISTIC PECULIARITIES OF T. SHEVCHENKO’S SLAVERY ELEGY “KHIBA SAMOMU NAPUSAT…” - Vivcharyk, N. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Т. Shevchenko’s poem “Khiba samomu napusat…” is analyzed as slavery elegy where the feelings of the narrator and the author are assonant. This is indicated by facts accordant with the writer’s biography: edition of “Kobzar” in 1840, exile, loneliness. It is analyzed the symbolism of Cossack, steppe, grave which create historical reminiscences and are found through out T. Shevchenko’s works. The image-related problems are analyzed in the article too.